Fair and Tender Data. The FAIRness of Four Databases With Historical Individual Life Course Data Tested - Lex Heerma van Voss (Historical Life Course Studies)
Four databases with data on individual historical life courses are tested for FAIRness: the TRA, Umeå, HSN and IPUMS databases. All databases make their data much more Findable than they were in the original sources. But as databases, they are best findable if their name is a unique acronym, and if different sub-datasets all use that same acronym. Sensitive data have to be protected. Two databases make anonymous data sets or those only containing information on deceased individuals Accessible without any formalities, and other databases could follow this example. To increase Interoperability a large number of tools are offered by the databases. Reusability is among the raisons d’être of these databases.